Investigation of Compact Low Pass Filter with Sharp Cut–Off using Metamaterial - Annaram, Karuppiah; Nithya, Suresh (Společnost pro radioelektronické inženýrství, 2013)
In this paper a new compact microstrip Bessel low pass filter (LPF) is experimentally validated using complementary split ring resonator (CSRR) which has sharper cut-off and improved spurious band suppression characteristics. The Richard’s transformation and Kuroda’s identities are used for realizing distributed Bessel LPF from the lumped element Bessel LPF. Traditionally Butterworth and Chebyshev LPFs are used in communication systems. Those LPFs exhibits high reflection in the pass-band and it is also very difficult to achieve sharper cut-off. Because of its poor cut-off and non linear phase characteristics, it will create cross talk between microwave systems. In order to overcome the above issues our proposed LPF which has linear phase and sharper cut-off behavior is on ideal subsystem in future microwave systems. Furthermore, to prove its practical viability of the proposed design, a compact microstrip Bessel LPF was designed, simulated, fabricated and measured. It was observed from the experimentally compared results of the proposed Bessel LPF with CSRR has better sharper cut-off characteristic than the without CSRR structure.
Keywords: Low-pass filter; spurious rejection; linear phase; complementary split ring resonators; resonators; microstrip filters; Bessel filter; microwave filters.